The current levels of 137Cs in foodstuffs of wild origin according to the results of the radiation-hygienic survey of the Bryansk region settlements - I. K. Romanovich; A. B. Bazyukin; A. A. Bratilova; G. Ya. Bruk; T. V. Zhesko; M. V. Kaduka; O. S. Kravtsova (Радиационная гигиена)
Introduction: In natural ecosystems included in food chains with humans as the final link, high levels of 137Cs were observed in the long-term period after the Chernobyl accident.   The objective of this study was to describe current levels of 137Cs in samples of foodstuffs from the Bryansk region settlements.   Materials and Methods: An analysis of data on the 137Cs concentration in 1837 samples of foodstuffs of wild origin from the Bryansk region settlements was taken. The 137Cs concentration were measured using gamma spectrometry methods.   Results of the Study and Discussion: Exceeding the permissible levels of 137Cs concentration was found in all main categories of food products: mushrooms (40 % of the studied samples do not satisfy radiation safety requirements), wild berries (55 %), meat of game (50 %), and local fish (18 %). The total percentage of such kind of samples was 43 %.   Conclusion: Foodstuffs of wild origin dominate internal exposure dose of residents at the present time. The main dose-forming foodstuff is wild mushrooms.